Foundational and translational research opportunities to improve plant health - Michelmore, R.; Coaker, G.; Bart, R.; Beattie, G.; Bent, A.; Bruce, T.; Cameron, D.; Dangl, J.; Dinesh-Kumar, S.; Edwards, R.; Eves-van den Akker, S.; Gassmann, W.; et al. (American Phytopathological Society, 2017)
This white paper reports the deliberations of a wo rkshop focused on biotic challenges to plant health held in Washington, D.C. in September 2016. Ensuring health of food plants is critical to maintaining the quality and productivity of crops and for sustenance of the rapidly growing human population. There is a close linkage between food security and societal stabil ity; however, global food security is threatened by the vulnerability of our agricultural systems to numerous pests, pathogens, weeds, and environmental stresses. These threats are aggravated by climate ch ange, the globalization of agriculture, and an over- reliance on non-sustainable inputs. New analytical and computational technologies are providing unprecedented resolution at a variety of molecular, cellular, organismal, and population scales for crop plants as well as pathogens, pests, beneficial microbes, and weeds. It is now possible to both characterize useful or deleterious variation as well as precisely manipulate it. Data-driven, informed decisions based on knowledge of the variation of biot ic challenges and of natural and synthetic variation in crop plants will enable deployment of durable in terventions throughout the world. These should be integral, dynamic components of agricultural strategies for sustainable agriculture.